Narrating Unity and Power: Economic Discourse as Ideological Text in President Prabowo’s D-8 Summit Speech - Nur Amalia Putri; Istanti Hermagustiana; Aridah Aridah (International Journal of Education, Vocational and Social Science, 2026)
Political speeches delivered in international forums may be read not only as policy statements but also as ideological texts that construct collective identity and narrate power relations. This article examines President Prabowo Subianto’s speech at the D-8 Summit as a literary-discursive artifact that articulates economic unity as a central ideological narrative of the Global South. Drawing on Norman Fairclough’s Critical Discourse Analysis, the study adopts a qualitative textual approach to analyze lexical patterns, repetition, modality, and evaluative language. The findings indicate that the speech employs economic statistics, historical allusions, and moral appeals to produce a narrative in which unity signifies strength, fragmentation signifies vulnerability, and cooperation becomes a moral and political obligation. References to justice, inclusivity, and solidarity with Palestine further position the D-8 within a shared postcolonial consciousness. The study argues that the speech functions as a narrative of resistance that reimagines economic cooperation as cultural and ideological power. By treating political discourse as a literary text, this article contributes to literary studies by demonstrating how language, ideology, and power intersect in contemporary global narratives.